Perceived Factors Affecting the Decision to Vaccination Against COVID-19 among Children aged 6 months to 4 years of Parents in Singhanakhon District, Songkhla Province - Samonkridsana, Arunsiri; Waichompu, Navarat (Princess of Naradhiwas University Journal, 2023)
The objectives of this research were 1) to study the perception factors of COVID-19 vaccination, 2) to study the decision to vaccinate against COVID-19, and 3) to study the perception factors of parents affecting the decision to vaccinate against COVID-19. The sample group was 172 parents, calculated by the G*Power program. The tool used was a questionnaire, received the IOC between 0.67-1.00 and the Cronbach’s alpha coefficient. at 0.85. Data were analyzed by descriptive statistics: frequency, percentage, mean, standard deviation. The analysis of cognitive factors affecting the decision to vaccinate against COVID-19 using step-by-step multiplicative regression showed as follows: 1. Factors of awareness of vaccination against COVID-19 in children aged 6 months to 4 years, the overview of each aspect and each item were at a high level. 2. The decision to vaccinate against COVID-19 in children aged 6 months to 4 years, the overview of each aspect and each item were at a high level. 3. Factors influencing the decision to vaccinate against COVID-19 were the perceived benefits of the vaccine (Beta=.358) and the safety and side effects of the vaccine (Beta=.176). The variance was 55.60% (adj.R2 = .556, p < .001), with a statistical significance at the .001 level and a standard error of prediction of .29396.